Application of the FDTD Method to the Analysis of Electromagnetic Wave Propagation in Systems with Concrete and Reinforced Concrete - Agnieszka Choroszucho; Tomasz Szczegielniak; Dariusz Kusiak; Anna Jaskot (Energies)
Wireless communication very often causes problems due to its quality. Problems with the network are very important when installing wireless networks inside buildings. The reason is the effects created during the propagation of electromagnetic waves inside rooms due to, among other factors, the construction of the walls and the building materials used. At the stage of network design, it is possible to use numerical methods, which allow for multivariate and fast analysis. This article presents a multivariate analysis of the impact of the variability in the electrical parameters of concrete and reinforced concrete on the propagation of electromagnetic waves and the value of the electric field intensity. The subject of the analysis was a wall composed of a homogeneous material (concrete) or non-homogeneous material (concrete with reinforcement). In the case of the homogeneous wall, the analysis was performed taking into account four electric permittivity values and a wide range of conductivity values. The analysis was performed at two frequencies used in wireless communication (2.4 GHz and 5 GHz). The analysis was performed using the time method based on Maxwell’s equations—the finite difference time domain method (FDTD). The results of the numerical analysis were compared with the results obtained from the presented analytical relationships. In the next step, four models and calculations were obtained for systems with a reinforced concrete wall, taking into account the variability in the spacing between the bars, the diameter of the reinforcement and the number of rows of reinforcement. The analysis of complex systems was performed at a frequency of 2.4 GHz. The aim of the presented analysis was to check how the change in the value of the electric permittivity of concrete affects the values of the field intensity and its effect on the analysis of systems composed of concrete with reinforcement. In the case of concrete, it was observed that, for conductivity above 0.9 S/m, regardless of the electric permittivity, all characteristics had a similar course. For low concrete loss, the greatest differences in the electric field intensity were observed at a frequency of 2.4 GHz rather than at 5 GHz. On the other hand, the analysis of systems with reinforced concrete showed, among other aspects, that models with two rows of bars and spacing of 0.15 m, regardless of the reinforcement diameter, were characterized by lower values of the electric field intensity compared to the variants with one row of bars.